Potrebuje evropsko kolizijsko pravo Uredbo Rim 0? - Tertnik, Simon (Pravnik, 2013)
The majority of European states private international law is nowadays regulated under European Unions regulations. The latter no longer ad-dress solely the single most burning issues of private international law, but are rather trying to shape a functioning system of the entire private international law. Within this frame, the paper at hand addresses the question of how the European private international law could and should develop in the future in order to become more systematic and harmonic, and to achieve a higher level of abstractness as well. The author explores which legal issues included in the European regulations are common to the entire private international law and form the so-called general part of private international law. By analysing individual issues the author tries to determine to what extent their unification in one regulation Rome 0 Regulation would be possible and useful. The author concludes that many of the analysed issues are suitable for unification. If carried out wisely, such unification could greatly contribute to the distinctiveness, transparency, and quality in general of the legal system.
Keywords: European Union; Evropska unija; kolizije zakonov; mednarodno zasebno pravo